Stretching EU competition law tools for search engines and social networks - Inge Graef (Internet Policy Review, 2015)
Because of their multi-sided and dynamic nature, the application of competition law to online platforms may prove challenging. The paper maintains that existing competition concepts are flexible enough to be adequately applied to search engines and social networks. It is argued that, in order to take the fast-moving nature of these industries into account, relevant markets should not be defined along strict product boundaries and that the strength of potential competition constitutes a better indicator for dominance than the size of market share. Such an approach would make competition analysis more conducive to innovation and would better recognise its role in the dynamic online intermediary sector.
Keywords: 300; Competition law; Search engine; Social network